Determinasi Minat Berzakat (Zakah-Philia): Peran Religiositas, Kepercayaan, Pelayanan, dan Pendapatan - Yeni Nuraeni (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2024)
The objectives of this study are: 1) To determine the influence of religiosity factors on people's interest in paying zakat at the Imam Bonjol Grand Mosque; 2) To determine the influence of trust factors on people's interest in paying zakat at the Imam Bonjol Grand Mosque; 3) To determine the influence of service factors on people's interest in paying zakat at the Imam Bonjol Grand Mosque; and 4) To determine the influence of income factors on people's interest in paying zakat at the Imam Bonjol Grand Mosque. This type of research is field research with quantitative methods. The population of this study is the muzakki of the Imam Bonjol Grand Mosque with a total of 80 respondents. This study uses a nonprobability sampling technique (convenience sampling) with an accidental sampling method. Data collection using questionnaires and analyzed using multiple linear regression through the SPSS 25 program. Based on the results of the analysis, it shows that the factors that influence Zakkah Philia are: Religiosity with a Sig of 0.009 (X1), Trust with a Sig of 0.923 (X2), Service with a Sig of 0.000 (X3), and Income 0.041 (X4)